The Inflammasome in Reproductive Biology: A Promising Target for Novel Therapies - de Rivero Vaccari, Juan Pablo (Frontiers in Endocrinology, 2020)
The inflammasome is a key regulator of innate immunity involved in the inflammatory response to infections as well as disease through the activation of caspase-1 and the processing of the inflammatory cytokines interleukin (IL)-1β and IL-18. Even though the inflammasome was first described in the context of infections, most research in recent years has focused on targeting the inflammasome as a therapeutic option in sterile inflammatory events. Recent evidence indicates a clear involvement of the inflammasome in Reproductive Biology such as infertility and preeclampsia. In this mini-review, I summarize the current findings on the inflammasome that have been described in the field of Reproductive Biology and highlight the potential that the inflammasome has as a novel therapeutic option in this field. The topics covered in this review as it pertains to the inflammasome field cover the literature published on male and female infertility, endometriosis, preeclampsia, placental inflammation, and reproductive senescence.